2022
DOI: 10.3991/ijet.v17i02.28543
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Influence of Invisible Knowledge Learning in Online Learning on Students’ Entrepreneurial Orientation

Abstract: Knowledge management is the inevitable product of the information age, and knowledge transformation is the result of the interaction between network learners and learning resources. The four aspects of the SECI (Socialization, Externalization, Combination, Internalization) model can help students accelerate their learning of entrepreneurial tacit knowledge in e-learning to realize the construction of entrepreneurial knowledge with entrepreneurial orientation as the core. Based on the SECI model, this paper pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The analysis of the teaching cluster discusses various perspectives on effective teaching methods to support online learning. In our analysis, teachers who use the tacit knowledge learning method have a positive effect on students' entrepreneurial orientation (Jing, 2022), where tacit knowledge is generally obtained through experience and self-learning, and is influenced by beliefs, perspectives, and values (Núñez-Canal et al, 2022). Furthermore, other studies have found that the demand for MOOCs (massive open online courses) in business and entrepreneurship classes is very large (Mozahem, 2021), and MOOCs play an important role in digitizing entrepreneurial learning (Dong &;Tu, 2021); (Yepes-Baldó et al, 2016), on the other hand, MOOCs are suitable platforms for teaching entrepreneurship because they provide tools to enable students' collaborative learning (Al-Atabi &;Deboer, 2014).…”
Section: The Primary Research Abstract and Author Collaboration Netwo...mentioning
confidence: 82%
“…The analysis of the teaching cluster discusses various perspectives on effective teaching methods to support online learning. In our analysis, teachers who use the tacit knowledge learning method have a positive effect on students' entrepreneurial orientation (Jing, 2022), where tacit knowledge is generally obtained through experience and self-learning, and is influenced by beliefs, perspectives, and values (Núñez-Canal et al, 2022). Furthermore, other studies have found that the demand for MOOCs (massive open online courses) in business and entrepreneurship classes is very large (Mozahem, 2021), and MOOCs play an important role in digitizing entrepreneurial learning (Dong &;Tu, 2021); (Yepes-Baldó et al, 2016), on the other hand, MOOCs are suitable platforms for teaching entrepreneurship because they provide tools to enable students' collaborative learning (Al-Atabi &;Deboer, 2014).…”
Section: The Primary Research Abstract and Author Collaboration Netwo...mentioning
confidence: 82%
“…Not a few were found in the experience of divorce, which caused children's education to be disrupted in contrast to children who received instruction in more developed areas and even in the city. With facilities and information that is easier to obtain, it is one of the factors that children are more enthusiastic about carrying out education at school [12] [13]. For example, the number of tutoring places available makes children compete to participate in tutoring outside to be younger when they get learning at school.…”
Section: Resultsmentioning
confidence: 99%
“…In the educational context, the motivation to the will power of students to perform academic activities (Di Serio, Ib añez, & Kloos, 2013), further, the level of student motivation reflects their commitment to attend and study the content of a program of study, as well as the student's desire to contribute, learn and accept the experience generated by the training program in the development of their profession (Zhang, 2022b).…”
Section: Knowledge Transfermentioning
confidence: 99%